Peningkatan Kemampuan Menarasikan Teks Wawancara dengan Teknik Pemodelan Siswa Kelas VII.4 SMPN 6 Bukittinggi - Jayanty, Venny; Chan, Wirsal; Ratna, Ellya (Universitas Negeri Padang, 2012)
The purpose of this study were to describe: (1) the process of narrating review text skill. (2) the improvement of the students skill in narrating a review text for students of VII.4 grade at SMP Negeri 6 Bukittinggi. The research data was collected by qualitative data were observation note, field note, questioner, and review, and quantitative data was collected based on test. Research finding of the process of narrating review text skill by modeling technic of students of VII.4 grade at SMP Negeri 6 Bukittinggi was run well. The average of student’s tests score increased from pre sickle until the second sickle, in pre sickle is 54.78, in the first sickle was 79.1, and in the second sickle was 90.5.